Digital journalism and the facilitation of hate - Perreault, Gregory P. (Disruptions: studies in digital journalism, 2023)
"Digital Journalism and the Facilitation of Hate explores the process by which digital journalists manage the coverage of hate speech and "hate groups", and considers how digital journalists can best avoid having their work used to lend legitimacy to hate. Leaning on more than 200 interviews with digital journalists over the past three years, this book first lays the foundation by discussing the essential values held by digital journalists, including how they define journalism; what values they consider essential to the field; and how they practice their trade. Perreault considers the problem of defining "hate" and "hate groups" by the media, acknowledging journalism's role in perpetuating hate through its continued ideological coverage of marginalized groups. Case studies, including the January 6 U.S. Capitol siege, the GamerGate controversy, and the Unite the Right rally in Charlottesville, help to elaborate on this problem and illustrate potential solutions. Digital Journalism and the Facilitation of Hate draws attention to the tactics of white nationalists in leveraging digital journalism and suggests ways in which digital journalists can more effectively manage their reporting on hate. Offering a valuable, empirical insight into the relationship between digital journalism and hate, this book will be of interest to students, scholars, and professionals of social and digital media, sociology, and journalism"--